Group interventions for children with autism spectrum disorders : a focus on social competency and social skills - Cotugno, Albert J. (Jessica Kingsley Publishers, 2009)
Given the significant core deficits in social interaction and communication that children with Autism Spectrum Disorder (ASD) demonstrate, it is critical to understand and develop interventions which directly address these needs. This book considers the theoretical and practical implications of developing and implementing peer-based, group-focused therapeutic approaches with children on the autism spectrum. Albert Cotugno describes the theoretical underpinnings of an intervention model based on cognitive developmental principles, and explains why a group approach is best suited to address and.